Proteolytic Sensitivity, In Vitro Glycation Efficiency of Diabetic and Non-diabetic Human Serum Albumin - Hadiya Husain; Riaz Ahmad (Avicenna Journal of Medical Biochemistry, 2022)
Background: Glycation of human serum albumin (HSA) leads to disturbances in its stability, activity, and other properties which, in turn, affect the functional properties of HSA. Modification of albumin by glycation shows considerable potential as a significant biochemical biomarker for diagnosing diabetes. The characteristics of the glycation process in proteins have not been fully examined yet and, therefore, there is insufficient knowledge about them in the field.